Fenomena Fomo dan Perilaku Konsumtif Generasi Z Perspektif Tafsir Al-Misbah: Analisis QS. Al-Isrā’: 26-27 tentang Larangan Isrāf - Siregar, Novalia Suriani; Junaidi, Junaidi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The phenomenon of Fear of Missing Out (FOMO) is one of the social characteristics commonly experienced by Generation Z. The rapid development of social media has intensified individuals’ tendency to feel left behind when they do not follow current trends. This condition encourages the emergence of excessive consumer behavior, which may lead to wasteful spending. This study aims to examine the phenomenon of FOMO and consumer behavior among Generation Z from the perspective of the Qur’an, with a focus on the interpretation of QS. Al-Isrā’ [17]: 26–27 in Tafsir Al-Misbah. This research employs a library research method with a descriptive qualitative approach. The findings indicate that consumer behavior influenced by FOMO is aligned with the concept of isrāf, which is prohibited in the Qur’an, referring to the excessive use of wealth beyond actual needs. The interpretation in Tafsir Al-Misbah emphasizes the importance of balance and wisdom in consumption as part of a Muslim’s moral and spiritual responsibility.